An in-situ reactive zone with xanthan gum modified reduced graphene oxide supported nanoscale zero-valent iron (XG-nZVI/rGO) for remediation of Cr(VI)-polluted aquifer: Dynamic evolutions of Cr(VI) and environmental variables. Issue 1 (February 2021) - Liu, Wanting; Bai, Jing; Chi, Zifang; Ren, Liming; Dong, Jun
Abstract: Xanthan gum (XG) as an excellent stabilizer has been utilized to enhance the stability of reduced graphene oxide-based nanoscale zero-valent iron (nZVI/rGO). However, Cr(VI) removal and environmental variable evolution of in-situ reactive zones using XG-nZVI/rGO as a remediation agent are not well understood. In this study, in-situ remediation of Cr(VI)-contaminated aquifer using XG-nZVI/rGO in three-dimensional sandbox was investigated. Results showed that XG-nZVI/rGO could form an in-situ reaction zone in the aquifer and effectively remove Cr(VI) downstream of the injection for 108 h. The injection of XG-nZVI/rGO could change the aquifer conditions from oxidizing into reducing environment by significantly reducing dissolved oxygen and oxidation-reduction potential of the reaction zone, which would provide favorable conditions for Cr(VI) removal. Meanwhile, solution pH of the aquifer did not fluctuate before and after XG-nZVI/rGO injection, indicating that remediation would not significantly change the acid-alkaline system. The process did not produce a great quantity of Fe 2+, which was toxic to environmental microorganisms. Graphical Abstract: ga1 Highlights: Evolution of Cr(VI) and environmental variables in in-situ reactive zone was investigated XG-nZVI/rGO injection resulted in environment transformation from oxidic into reductive Acid-alkaline property was relatively stable before and after XG-nZVI/rGO injection Mechanism of Cr(VI) removal using XG-nZVI/rGO was proposed